FUNCTIONAL STATUS OF THE HYPOTHALAMIC-PITUITARYGONADAL AXIS IN OPERATED WOMEN WITH CUSHING'S SYNDROME PATIENTS 1,3,6 MONTHS AFTER SURGICAL TREATMENT - Zamira Yusufovna Khalimova; Oydin Bahadirova Irgasheva (Scholar Express Journal, 2021)
Under observation by the staff of the Department of Neuroendocrinology and Neurosurgery of the RSNPMC of Endocrinology, M3 RUz and RKK for Cushing's Syndrome, 163 patients of fertile age have been registered from 2000 to the present time. Mean age was 27.58±3.4 years (from 17 to 49 years). The average duration of the disease was 4.2 ± 0.2 years. Twenty healthy women of the same age formed a control group. All female patients with SC registered since 2000 (deceased were not included) were distributed by etiology as follows: 1 gr. - patients with ACTH-dependent SC - 130 (79.7%), 2 gr. - with ACTH-independent SC - 30 (18.4%), and group 3 - patients with ACTH-ectopic SC - 3 (1.8%). Before treatment, women with SC in group 1 had a significant increase in basal ACTH, cortisol, prolactin against the background of hyperandrogenemia and ovarian insufficiency (p<0.05). In patients with IC in groups 2 and 3, a significant increase in basal values of cortisol, prolactin, and hyperandrogenemia (p><0.05) was associated with a non-significant decrease in estradiol and progesterone (p>0.05). In patients with SC with surgical treatment in 1, 2 and groups, normalization of ACTH and cortisol levels was seen 1 month after surgery, but after 6 months the condition remained practically unchanged, p < 0.05. One year after surgery we found normal blood hormone levels of ACTH, LH, FSH, cortisol, prolactin in the patients of all three groups
Keywords: ACTH-dependent Cushing's syndrome; ACTH-independent Cushing's syndrome; pituitary adenoma